FRI0287 BIOLOGIC DRUG RESPONSE DOES NOT APPEAR RELATED TO RADIOGRAPHIC STATUS IN AXIAL SPONDYLOARTHRITIS: DATA FROM THE BSRBR-AS REGISTRY. (13th June 2020) - Michelena, X.; Zhao, S. S.; Dubash, S.; Jones, G. T.; Dean, L.; Marzo-Ortega, H.
Abstract : Background: The concept of axial spondyloarthritis (axSpA) incorporates the full range of inflammatory spinal disease. In the absence of specific immuno-genetic biomarkers, classification criteria differentiate two groups (non-radiographic [nr-axSpA] and radiographic axSpA [r-axSpA]) based on the presence of structural damage of the sacroiliac joints. Controversy remains as to whether nr-axSpA represents a milder form with biologic DMARD (bDMARD) treatment restrictions still in place in many countries. Objectives: To describe the baseline characteristics and bDMARD response at one year in axSpA patients in the British Society for Rheumatology Biologics Register in Ankylosing Spondylitis (BSRBR-AS) according to radiographic status. Methods: BSRBR-AS is a national prospective cohort including participants who fulfil the ASAS classification criteria for axSpA. In this analysis, cross-sectional baseline data of patients starting bDMARDs including clinical, demographic and patient-reported outcomes (PROs) were compared. Follow-up data at one year was identified if 12±4 months from baseline and PROs completed within 2 months of visit date. Ankylosing Spondylitis Disease Activity Scores (ASDAS) for low disease status, clinically important improvement (CII) and major improvement (MI) were used to assess treatment response. Results: Baseline characteristics were available for 1, 145 patients. Those with r-axSpA were more likely to be male, were older, and had longer disease duration (Table 1). Follow-up ASDAS was available in 290 patients. Two thirds of the patients achieved ASDAS low disease state at one year regardless of radiographic status (nr-axSpA: 64.2% vs r-axSpA: 66.1, Diff: -1.9%, 95% CI -13.7 to 9.8). Further, no significant differences were seen between the groups in attaining ASDAS CII (nr-axSpA: 50.7% vs r-axSpA: 44.7%, Diff: 6.0%, 95% CI -7.8 to 19.8%) or MI (nr-axSpA: 20% vs r-axSpA: 18.7%, Diff: 1.3%, 95% CI -9.7 to 12.3%). Conclusion: Although there appeared to be some differences in the baseline characteristics when exploring this cohort, according to radiographic status, which are likely related to the natural history of the disease; the level of biologic response was comparable between the groups supporting the concept of axSpA as a single disease entity. Acknowledgments: This project is supported by a FOREUM fellowship. Disclosure of Interests: Xabier Michelena: None declared, Sizheng Steven Zhao: None declared, Sayam Dubash: None declared, Gareth T. Jones Grant/research support from: Pfizer, AbbVie, UCB, Celgene and GSK., Linda Dean: None declared, Helena Marzo-Ortega Grant/research support from: Janssen, Novartis, Consultant of: Abbvie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, Takeda, UCB DOI: 10.1136/±annrheumdis-2020-eular.3147